MERUZHAN ASLANYAN – THE ESTIMATION OF THE IMPACT OF VARIOUS SHOCKS ON REMITTANCES FROM RUSSIA TO ARMENIA - Aslanyan, Meruzhan (Bulletin of Yerevan University G: Economics, 2021)
The inflow of remittances into Armenia’s GDP has a large share, therefore it is important to assess the extent to which various external factors affect remittances, whose change in the volume leads to changes in income of a certain part of the population, to some extent affects foreign exchange market developments. Since Russia accounts for more than 50% of remittance inflows to Armenia, this article evaluates a model using variables describing the Russian economy and the global oil market, taking into account the rolе of oil in the Russian economy.